Analisis Konten Visual Instagram dalam Membangun Keterlibatan Pelanggan: Studi Kasus Akun Instagram X Food and Beverage - Nur'ain Suleman; Rizan Machmud; Syamsul B. Biki (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Amidst the rapid growth of the culinary industry, Instagram has become a primary brand communication instrument that demands visual excellence to attract audiences. This study aims to analyze the role of visual aesthetics on the X Food and Beverage Instagram account in shaping customer engagement. Using a descriptive qualitative method with a case study approach, data were collected through in-depth interviews with seven informants (management, admins, and loyal consumers) and visual documentation of the research object. The analysis examined visual elements such as the earth-tone color palette and minimalist composition through semiotic theory. The findings indicate that consistent visual usage successfully established a strong brand identity and provided a sense of mindfulness for the audience, effectively increasing trust in product quality. However, a "perfection paradox" was identified, where overly professional visuals created a psychological barrier for consumers to interact actively in the comments section, despite high physical visitations. In conclusion, the integration of high aesthetics and authentic human interest is key to maintaining consumer loyalty in the digital era. This research implies the need for a balance between aesthetic ego and open communication spaces to create an inclusive customer community.